Mapping Study of Design Thinking on Product Development in The Last 10 Years - Ajeng Putri Hanifah; Iwan Sukoco; Anang Muftiadi (Penerbit Goodwood, 2023)
Purpose: The availability of literature regarding design thinking concerning product development in recent years has not been able to be synthesized. So, this article is expected to be able to provide the development of a conceptual framework that can categorize how design thinking contributes to product development and provides a mapping presentation to visualize how research in the field of design thinking studies on product development has developed in the last 10 years. Methodology/approach: A systematic analysis was carried out on articles published in the last 10 years. Results/findings: Produce a conceptual frameworj that provides a typology to discuss the development of how design thinking contributes to the product development ecosystem and directs research for the future. Limitations: This article has limitations, first regarding evidence from articles that provide different perspectives and also topic of discussion. Second, the result obtained from the literature review are greatly influenced by use of keywords. Third, this study did not carry out an analysis related to the impact of the article through citation analysis. Contribution: This study responds to the increasing interest in design thinking and the rapid growth in the proliferation of studies by providing a review of design thinking and its relation to product development that has occurred over the last 10 years. Keywords: design thinking, product development, mapping study